Penyuluhan Proses Sertifikasi Halal Pada Pelaku UMKM Kota Metro - Mardiantari, Ani; Dwilestari, Ita; Ibrahim, Maulana Malik (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
People's behavior when buying products is sometimes only based on orientation towards the product they like. In line with the implementation of the Halal Product Guarantee Law Number 33 of 2014, one of the articles of which states that all products, whether originating from animal, plant or raw materials produced through chemical processes, must be certified halal, the halal awareness of these products is increasing. the presence or absence of non-halal components is absolutely necessary. Therefore, it is very necessary to provide education about the halal certification process through community service programs. The aim of this counseling is to provide knowledge and understanding to participants about the importance of halal certification for Micro, Small and Medium Enterprises (MSMEs), provide insight into the influence of halal certification on product buyer satisfaction and create a sense of security for consumers so that this is expected to motivate participants who owning a business, carrying out halal certification for its products is also increasing, as well as developing experience regarding the process of submitting a halal certification process to LPPOM MUI.